Single injection digital anaesthesia: an easy technique for paediatric finger injuries. Issue 12 (25th November 2008) - Jaiganesh, T; Barling, J; Parfitt, A; Criddle, J
Abstract : The novel use of a single injection digital anaesthesia technique in children is described, which was found to be effective.